Reliability and accuracy of skin-supported surgical templates for computer-planned craniofacial implant placement, a comparison between surgical templates: With and without bony fixation. Issue 6 (June 2019) - Dings, J.P.J.; Verhamme, L.; Maal, T.J.J.; Merkx, M.A.W.; Meijer, G.J.
Abstract: Introduction: The purpose is to determine the accuracy of guided implant placement in the orbital, nasal, and auricular region using computer-aided designed stereolithographic skin-supported surgical templates with and without bone fixation pins. Materials and Methods: Preoperatively, cone-beam CT (CBCT) and multiple detector computed tomography (MDCT) scans were acquired from 10 cadaver heads, followed by virtual planning of implants in the orbital margin, auricular region and nasal floor. Surgical skin-supported templates were digitally designed to allow flapless implant placement. Fixation pins were used for stabilization comprising half of all templates in predetermined bone areas. The accuracy of the surgical templates was validated by comparing the achieved implant location to its virtual planned implant position by calculating the linear and angular deviations. Results: Surgical templates with the use of bone fixation pins produced statistically significant greater implant deviations as compared to the non-fixated surgical templates. Conclusion: The results of this study indicate that significant deviation has to be taken into account when placing cranio-maxillofacial implants using skin-supported surgical templates. Surprisingly, the use of bone-fixated pins worsened the accuracy.